2005
DOI: 10.1055/s-2005-870156
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in the Genetics of Adrenocortical Tumors, Pheochromocytomas and Paragangliomas

Abstract: Correspondence Pr. J. Bertherat´Service des Maladies Endocriniennes et MØtaboliques, Hôpital Cochin, Pavillon Cornil2 7, rue du Faubourg Saint−Jacques´75014, Paris´France´Phone: +33 (1) 58 41 18 95´Fax: +33 (1) 46 33 80 60É −Abstract Recent advances in the molecular genetic of adrenal tumors give new insights in the pathophysiology of these neoplasms in both hereditary and sporadic cases. The practice of genetic counsel− ling in patients with adrenal tumors have been recently changed by the identification and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…A recent retrospective study of 84 apparently sporadic pheochromocytoma showed that 12% of the patients had germ-line mutations of the VHL and succinate de- hydrogenase subunit B (SDHB) genes. Moreover, the identification of a mutation in SDHB gene was indicated as a high risk factor for extra-adrenal location of paraganglioma and for malignant disease [24]. The present patient was not definitely diagnosed as malignant pheochromocytoma at time of first surgery.…”
Section: Discussionmentioning
confidence: 77%
“…A recent retrospective study of 84 apparently sporadic pheochromocytoma showed that 12% of the patients had germ-line mutations of the VHL and succinate de- hydrogenase subunit B (SDHB) genes. Moreover, the identification of a mutation in SDHB gene was indicated as a high risk factor for extra-adrenal location of paraganglioma and for malignant disease [24]. The present patient was not definitely diagnosed as malignant pheochromocytoma at time of first surgery.…”
Section: Discussionmentioning
confidence: 77%
“…The occurrence of these tumors in familial settings, their association with hereditary syndromes, and their genetic alterations revealed that some cases are familial [7,8] . Multiple endocrine neoplasia type 2 (MEN2), neurofibromatosis type 1 (NF1) and von Hippel Lindau (VHL) syndrome subtypes 2A, 2B, and 2C account for about 10% of cases; the genes involved being the RET proto-oncogene and the NF1 and VHL tumor suppressor genes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple endocrine neoplasia type 2 (MEN2), neurofibromatosis type 1 (NF1) and von Hippel Lindau (VHL) syndrome subtypes 2A, 2B, and 2C account for about 10% of cases; the genes involved being the RET proto-oncogene and the NF1 and VHL tumor suppressor genes, respectively. However, with the identification of the familial paraganglioma syndromes, characterized by mutations in the subunits of the succinic dehydrogenase (SDH) enzyme (Table 2, Note: The syndromes were named in the order in which they were identified) [8] , it now appears that over 30% of cases are associated with an inherited genetic disposition [8][9][10] . In our investigation, a very high malignancy rate of 19.74% was obtained, which may suggest that a significant proportion of these patients may have underlying familial SDH gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary paragangliomas are multicentric in 20%-50% of cases [8,9] , whereas sporadic paragangliomas are multicentric in 10% of cases. In hereditary cases, they may be associated with multiple endocrine neoplasia type 2, von Hippel-Lindau disease, familial paraganglioma, Carney triad and neurofibromatosis type 1 [10] . For this reason, especially in patients diagnosed before 50 years of age and in those who present with bilateral, multifocal, and malignant paragangliomas, genetic testing may be beneficial [11] .…”
Section: Discussionmentioning
confidence: 99%